The Role of B-Lines on Transthoracic Ultrasonography in Patients of Interstitial Lung Disease - Qureshi, Afshan; Ayyaz, Salman; Hanif, Asif; Nasir, Yasir; Saeed, Muhammad Saqib (Annals of King Edward Medical University, 2020)
Background: Gold standard for the diagnosis is High Resolution Computed Tomography (HRCT). It provides all detailed morphological depiction of a minimal interstitial lung involvement. However exposure to radiation, high cost and non-availability are its few limitation. Ultrasound chest can play a complimentary part in the disease evaluation. Objective: To determine the role of B lines on transthoracic ultrasonography in patients of known interstitial lung disease. Methods: This study was carried out in Institute of TB & Chest Medicine, Mayo Hospital / KEMU Lahore and it continued over a period of six months. About 50 patients of mean age of 50 + 15 years (27 female and 23 males) with known Interstitial Lung Disease (ILD) underwent chest ultrasound for assessment of presence of B-lines and distance between them was measured. These findings compared with that of HRCT findings Ground Glass Opacity (GGO), reticular pattern involving sub pleural region, nodules, honey combing etc). Results: All patients had bilateral B-lines as they were all diagnosed cases of ILD, the distance between two adjoining lines correlated well with their disease process shown on HRCT where B3 correlated with GGO and B7 correlated with pulmonary fibrosis and honey combing. Study had 22 Non Specific Interstitial Pneumonitis (NSIP) patients, 14 of Idiopathic Pulmonary Fibrosis (IPF), 5 of Sarcoidosis, 4 of Hypersensitivity pneumonitis, 4 of Connective tissue disorder and 1 of Cryptogenic Organizing Pneumonia (COP). Conclusion: B-lines that are lung ultrasound sign of extensive interstitial pathology seem to be useful in the assessment of ILD as significant correlation was found between lines on ultrasound and HRCT findings.